2016
DOI: 10.20961/prasasti.v1i2.1914
|View full text |Cite
|
Sign up to set email alerts
|

Afiks-Afiks Pembentuk Verba Denominal Dalam Bahasa Jawa

Abstract: Research purposes are (1) to identify affixes in Javanese language which form denominal verbs and to explain the functions and meanings of javanese verbal derivation, and (2) to explain productivity of derivative affixes in forming denominal verbs in Javanese languange. The theoritical basis used in the research covers (1) morphology, (2) verbs, (3) affixes, (4) derivational morphology, (5) inflectional morphology (6) kinds of Javanese derivations, and (7) productivity of affixes in Javanese verbs. This resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…The study conducted by Sutjiati shows that such affixes survive in spite of a number of innovations or changes. Erawati (2002) explored "the Inheritance of the Old Javanese language affixes in the Modern Javanese language" using the comparative historical linguistic theory and the distinctive features of the generative phonological theory. She found that a number of affixes are inherited with some changes and another number of affixes disappear.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The study conducted by Sutjiati shows that such affixes survive in spite of a number of innovations or changes. Erawati (2002) explored "the Inheritance of the Old Javanese language affixes in the Modern Javanese language" using the comparative historical linguistic theory and the distinctive features of the generative phonological theory. She found that a number of affixes are inherited with some changes and another number of affixes disappear.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Prefiks merupakan imbuhan yang diletakkan di awal kata dasar, infiks merupakan imbuhan yang diletakkan di tengah kata dasar, sufiks merupakan imbuhan yang diletakkan di akhir kata dasar, dan konfiks merupakan sebuah imbuhan yang diletakkan di akhir kata dasar (Herawati et al, 2016).…”
Section: A Pendahuluanunclassified
“…Previous studies have extensively investigated the construction of languages, particularly in the realm of direct-motion verb, conducted by various researchers (Subiyanto, 2010;Maghfiroh, 2021;Ummah, 2018;Muttaqin, 2019;Putri & Subiyanto, 2023;Pamphila, 2011;Khasanah & Subiyanto, 2020). Subiyanto (2010) has already examined the construction of motion verb in Javanese language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using Talmy (1985) typological language, this research ultimately finds that Javanese language can be classified as verb-framed language due to its lack of resultative-adjective constructions. On the other hand, Muttaqin (2019) focuses on analyzing direct motion verb in Banjar language. Using descriptive- Talmy (1985) typological approach, this research finds that Banjar language can be classified as satellite-framed language because of its resultative-adjective.…”
Section: Literature Reviewmentioning
confidence: 99%